A dimensão urbana da arquitetura : ambientes de transição - Rosetti, Tamara Sofia Guanaes Silva (2012)
The present work aims to discuss the urban dimension of architecture and to investigate the role of the architectural spaces in the quality of life in between buildings and their environments. It investigates the transitional spaces between building and t